Prime-boost immunisation against tropical theileriosis with two parasite surface antigens: evidence for protection and antigen synergy. - Gharbi, M; Darghouth, M; Weir, W; Katzer, F; Boulter, N; Adamson, R; Gilbert, S; Jongejan, F; Westbroek, I; Hall, R; Tait, A; Shiels, B (2011)
Current methods for control of tropical theileriosis in cattle suffer from several disadvantages that could be circumvented by development of an effective sub-unit vaccine. Previous work has utilised two major surface antigens (SPAG-1 and Tams1) and conventional adjuvants to provide partial protection against parasite challenge. In this study we have delivered these antigens using the prime-boost system and analysed whether a combination regime can enhance protection against lethal challenge. Delivery of the boost as recombinant protein or expressed from a recombinant MVA vector was also assessed. The results confirmed that immunisation with Tams1 alone could reduce the severity of several disease parameters compared to non-immunised controls and these effects were more marked when recombinant protein was used for boosting compared to MVA delivery. A similar outcome was obtained by immunisation with SPAG-1 alone. Significantly, delivery of SPAG-1 and Tams1 as a cocktail showed enhanced protection. This was manifest by significant improvement in a large range of clinical and parasitological parameters and, most dramatically, by the survival and recovery of 50% of the immunised animals compared to 0% of the controls. Analysis of the antibody response post-challenge showed that while there was a strong response to Tams1, no response to SPAG-1 was detected. In contrast, lymphoproliferation assays showed a significant enhancement of response at day 7 post-challenge in calves of the SPAG-1 group but a dramatic decrease of the proliferation activity in all three groups receiving Tams1. We conclude that immunisation with a cocktail of SPAG-1 and Tams1 generates a synergistic protective response that significantly improves the efficacy of recombinant vaccination against tropical theileriosis. Potential effector mechanisms that could mediate this response are discussed.